Biochar-fertilizer mixture: does plant life history trait determine fertilizer application rate?. Issue 1 (31st December 2023) - Achakzai, Abdul Ghani; Gul, Shamim; Buriro, Abdul Hanan; Khan, Hidayatullah; Mushtaq, Ayesha; Bano, Amna; Agha, Sadiq; Kamran, Kashif; Ponya, Zsolt; Ismail, Tariq
ABSTRACT: The annual cumin and perennial fennel are economically important medicinal crops of cold dry regions of Pakistan. We hypothesized that the cumin, which produces 2–3 times less biomass, will respond to lower rates of mixture of biochar with synthetic NPK fertilizer or manure, compared to fennel. The NPK, poultry manure and their mixture with wood-derived or cow manure-derived biochars were applied for three consecutive years. No positive relation between application rate of biochar-mixed fertilizers and yield of both crops was observed over three years of study, except that manure-derived biochar-NPK mixture had a positive relation ( R 2  = 0.99, P = 0.01) with the yield of fennel only during the third year. Significant positive influences of biochar-based fertilizers compared to control were observed for cumin and fennel of third year cropping. The co-amendment of NPK (0.14 kg ha −1 ) with manure-derived biochar (6.6 t ha −1 ) consistently increased the yield of cumin during the first two years of cropping, as opposed to NPK fertilizer. Cumin had a greater seed:stover biomass ratio when it received the co-amendment of wood-derived biochar with NPK or poultry manure. Our findings indicate that there is some potential for biochar-fertilizer amendments to improve the growth of these high-value medicinal crops.